Building Brand Identity and Brand Awareness of RSKGM FKG UI through Social Media Re-Branding - Sari, Lusiana Puspita; Iswanto, Samto Hadi (Dinasti Publisher, 2025)
RSKGM FKG UI is the Main Dental and Oral Specialist Teaching Hospital for the Faculty of Dentistry, University of Indonesia which has been Fully Accredited on December 22, 2022 by the Indonesian Health Facility Accreditation Institute. RSKGM FKG UI is a Class A National Referral Hospital which has officially been operational since June 2002 until now. RSKGM FKG UI requires a brand identity to differentiate it from other RSKGM. For this reason, media is needed to promote RSKGM FKG UI so that it can be introduced to the wider community. The problem faced is the management of promotional media which is still not optimal. RSKGM FKG UI must have a strong logo in presenting the institution's brand identity. A brand logo with visual identity and the use of the right color palette can be applied to social media such as Instagram & Tiktok. This study uses a qualitative research method by studying books and references from various sources both from the internet, previous research studies, literature reviews, SWOT analysis (strength, weakness, opportunities, threats) aims to identify the overall strengths, weaknesses, opportunities, and threats of RSKGM FKG UI and can highlight the uniqueness of RSKGM FKG UI which is not owned by other hospitals or dental clinics. This research method is used in order to build public trust in RSKGM FKG UI as a leading dental hospital in Indonesia. With the existence of a strong brand identity and brand awareness through re-branding of existing social media, it is hoped that it can increase the number of patients who trust dental and oral health care by using the services at RSKGM FKG UI, so that it will have an impact on increasing income and also the welfare of the RSKGM FKG UI hospitalia community.